Utilização de carvão comercial e biochar proveniente de borra de café gasta na adsorção de octocrileno - Rocha, Sandra Andreola Franco da (2024)
The emerging pollutant octocrylene is not efficiently removed from effluents by conventional treatment, and is frequently found in rivers. In this study, the adsorption of octocrylene was evaluated using commercial charcoal and biochar from coffee grounds activated with ZnCl2. During experimental planning, the amount of octocrylene used was essential to ensures an efficiency of almost 100% in pollutant removal, allowing excellent adsorption for both coals. However, the adsorbent mass only interfered in tests with commercial charcoal. The kinetics showed adsorption of the contaminant in 40 minutes for both adsorbents, in which the first and second order models adjusted to the experimental data for octocrylene at 600 µg.L-1. Equilibrium isotherm tests demonstrated good correlation with experimental data. The model with the best adjustments and adsorption capacity was Langmuir for biochar, with a capacity of 37,822 ± 0.005 µg.mg-1 compared to 33,602 ± 0.202 µg.mg-1 for commercial charcoal. Furthermore, a toxicity analysis of a 600 µg.L-1 octocrylene solution was carried out before and after adsorption with the two charcoals separately on Allium cepa roots. Before adsorption, the solution was phytotoxic and cytogenotoxic in the bioassay. After adsorption, the solution obtained for each charcoal no longer caused toxicity to the roots. The coals had high removal efficiency and adsorption capacity, a condition reiterated by the toxicity results. However, biochar better represented the Langmuir model in the adsorption process when removing octocrylene from the aqueous medium.